Uncovering disease determinants of Covid-19 through analysis of its molecular evolution - Muthanje, Eric M.; Amwoma, Joseph G.; Kituyi, Sarah N. (African Journal of Biological Sciences, 2020)
Covid-19 was first reported in Wuhan China but has now spread globally with overwhelming impacts on human health and health systems. The disease is caused by the SARs-Cov-2 which is related to the SARs-Cov-1 that causes SARs. There is evidence suggesting that the virus originated from the Rhinolophilid bats and has subsequently undergone recombination to allow for a natural selection for a human host and it is thought that the recombination might have occurred either prior or upon infection of the human host. These events of natural selection are presumed to have hastened human to human transmission. However, analyses of sequences from Covid-19 isolates from China and across the globe point to a unique case scenario that may suggest selection and evolution of the virus upon infection of the human host. In this paper we have examined the role of the human ACE-2 receptor in determining the predisposition to Covid-19 and analyzed Covid-19 sequences deposited in the virus database from around the globe to provide evidence that the disease burden is different across regions and among individuals as determined by the genetics of the virus and that the virus is rapidly evolving across regions and populations. Our phylogenetics data confirms that all strains circulating around the globe are related to the strains from China, the origin of the virus and further depicts varying degrees of similarity and disparity which suggests that the virus is mutating. While the USA has already been shown to have sequences closely related to the Wuhan sequences, here we report that the sequences from Spain and Africa are distantly related to the Wuhan sequences. Owing to the unique presentation of the disease in regions across the globe, the summary presented here informs of the need to tailor the management of the disease as dictated by viral and host genetic factors and the observed regional burden of the disease.
Keywords: SARs-Cov-1; ACE-2; mutation; phylogenetics; disease burden